APPLICATION OF THE 1958 NEW YORK CONVENTION IN THE REPUBLIC OF UZBEKISTAN: PUBLIC POLICY, ARBITRABILITY, AND THE LIMITS OF SUBSTANSIVE REVIEW IN THE ENFORCEMENT OF FOREIGN ARBITRAL AWARDS - Normurodova Guzalkhon Nabijon kizi (Scholar Express Journals, 2025)
This article is devoted to the analysis of the application of the provisions of the 1958 New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards in the Republic of Uzbekistan. The paper examines the methods and structures for implementing the provisions of the 1958 New York Convention in the enforcement of arbitral awards, emphasizing three key categories: public policy, arbitrability, and the limits of substantive review. The article analyzes the legal framework governing the enforcement of foreign arbitral awards and highlights the relationship between international and national legal norms.
Keywords: International arbitration; public policy; 1958 New York Convention